1999
DOI: 10.2307/3343128
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Cost-Effectiveness of Linking the Special Supplemental Program for Women, Infants, and Children (WIC) and Immunization Activities

Abstract: This controlled intervention trial of screening, referral, and a voucher incentive in the WIC program demonstrated a substantial increase in immunization coverage at a low cost. Continuing to design linkages between WIC and immunization programs by building on WIC's access to at-risk populations is worth the investment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 1 publication
2
35
0
Order By: Relevance
“…[168][169][170] In addition, only seven studies reported one or more centre-specific characteristics such as the volume of cases they treat. 166,[173][174][175][176]196,197 These results are perhaps as expected, and it can be argued that authors would not normally be expected to provide such information. However, any reasonable assessment of the extent to which results found in a combination of locations apply to a particular location (within or outside the trial) requires information on what types of centres were included in a study and how trial patients compare with non-trial patients.…”
Section: Study Reportingsupporting
confidence: 61%
See 2 more Smart Citations
“…[168][169][170] In addition, only seven studies reported one or more centre-specific characteristics such as the volume of cases they treat. 166,[173][174][175][176]196,197 These results are perhaps as expected, and it can be argued that authors would not normally be expected to provide such information. However, any reasonable assessment of the extent to which results found in a combination of locations apply to a particular location (within or outside the trial) requires information on what types of centres were included in a study and how trial patients compare with non-trial patients.…”
Section: Study Reportingsupporting
confidence: 61%
“…The most frequently reported were age (65%), gender (56%), disease severity (38%) and co-morbidities (24%). However, only two studies 166,167 assessed the representativeness of the study sample to the study population in the trial centres.…”
Section: Inclusion/exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…15 Only 2 studies included in the current review 23,24 overlapped with studies in the NICE review. Other studies identified in the NICE review as "incentives" did not meet our definition because they either involved changing the frequency of attendance for welfare benefits but not the level of benefit itself [33][34][35] or did not involve incentives with real material value. 36 Similar to the current review, the NICE review concluded that incentives could be effective but that the strength and quality of the evidence varied, and costeffectiveness data were insufficient.…”
Section: Comparison Of Results With Previous Reviewsmentioning
confidence: 99%
“…These strategies are recommended by the Task Force for Community Preventive Services 31 and have been documented in numerous studies to produce improvements in vaccination coverage among children participating in WIC. [32][33][34][35] Improving the enrollment of pregnant women into WIC-based interventions can have an especially important impact on infant immunization status at 3 months. Furthermore, participation in WIC provides important nutritional benefits to the mother and infant.…”
Section: Discussionmentioning
confidence: 99%